2013
DOI: 10.1002/wcc.250
|View full text |Cite
|
Sign up to set email alerts
|

NIMBYism revisited: public acceptance of wind energy in the United States

Abstract: The acronym NIMBY, known to stand for ‘Not‐In‐My‐Back‐Yard’, generally describes resistance to siting specific projects close to one's area of residence while exhibiting acceptance of similar projects elsewhere. As wind energy continues to be recognized as a successful technology for meeting renewable energy targets and decreasing carbon dioxide emissions, the siting of wind turbines is a growing challenge that policy makers, facility planners, and wind developers face. The most often cited motivations for pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 147 publications
(631 reference statements)
2
79
0
5
Order By: Relevance
“…As such, the report underlines the need for a better understanding of the drivers of wind facility acceptance among affected communities (USDOE, 2015). This recommendation echoes the calls of numerous social scientists, who have suggested that successful implementation of U.S. wind projects relies on a deeper understanding of local stakeholders (e.g., Petrova, 2013).…”
Section: Background and Motivationsupporting
confidence: 64%
See 4 more Smart Citations
“…As such, the report underlines the need for a better understanding of the drivers of wind facility acceptance among affected communities (USDOE, 2015). This recommendation echoes the calls of numerous social scientists, who have suggested that successful implementation of U.S. wind projects relies on a deeper understanding of local stakeholders (e.g., Petrova, 2013).…”
Section: Background and Motivationsupporting
confidence: 64%
“…In the United States, federal production incentives for wind energy have required a significant tax liability, tipping the scales toward large private developers of wind projects (Bolinger, 2005). Some studies have demonstrated that community ownership is correlated to higher support and more positive attitudes toward wind energy in Europe and other regions (Krohn & Damborg, 1999;Maruyama et al, 2007;Petrova, 2013;Warren & McFadyen, 2010). One may reasonably expect some differences in perceptions and acceptance of wind energy in North America in relation to the low level of community ownership in the region.…”
Section: Justification For North American Focusmentioning
confidence: 99%
See 3 more Smart Citations